Fungal Nanotechnology 2.0 (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Fungal Nanotechnology 2 provides an updated and thorough explanation of the green and sustainable production of metal- and organic-based nanostructures by various fungal species, as well as an investigation of intracellular and extracellular mechanisms, with a particular focus on the applications of fungal nanotechnology in biomedical, environmental, and agri-food sectors. Since FN is still in its infancy, major research should be conducted in this field; plants, animals, and people will all benefit significantly from this, and effective and environmentally acceptable methods should be developed.